12x-3(x+4)=9x-9

Simple and best practice solution for 12x-3(x+4)=9x-9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12x-3(x+4)=9x-9 equation:


Simplifying
12x + -3(x + 4) = 9x + -9

Reorder the terms:
12x + -3(4 + x) = 9x + -9
12x + (4 * -3 + x * -3) = 9x + -9
12x + (-12 + -3x) = 9x + -9

Reorder the terms:
-12 + 12x + -3x = 9x + -9

Combine like terms: 12x + -3x = 9x
-12 + 9x = 9x + -9

Reorder the terms:
-12 + 9x = -9 + 9x

Add '-9x' to each side of the equation.
-12 + 9x + -9x = -9 + 9x + -9x

Combine like terms: 9x + -9x = 0
-12 + 0 = -9 + 9x + -9x
-12 = -9 + 9x + -9x

Combine like terms: 9x + -9x = 0
-12 = -9 + 0
-12 = -9

Solving
-12 = -9

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 10r^2-16r+120=0 | | 5(9x-3)+11=7x-9 | | 2(t-5)+8t=5(2t+3)-9 | | u^2-12u+25=0 | | x-3-4=10 | | x^2-9x-90= | | 4x+20-2x+15=85 | | 6x+ln(3x)=ln(19) | | 16x=17x+6 | | 10/8(5x+3)=-1 | | 4(a-4)=2a-1(-2a+4) | | 4x+7=0+3x | | 11/11(11x+11)=-3 | | 1.496=2.380p+0.250 | | 5x/5-3=9 | | 977.62-128.41= | | 18x^2-15x-24= | | 6x-4+3x+5x+8=180 | | 11/5(4x+5)=1 | | 5x^2+17x+9=0 | | -3x+5=2x+55 | | -6v-1=3-2v | | 2w+(42-2w)=42 | | 5+2=57 | | 0.7x+3.5=33.4 | | 7+3(x-4)-10=45 | | 3-5x-4x=48 | | 2r-2(5+r)=6+2r | | 2n+1-3n=7+2n+3n | | -8+6x-4x=-22 | | 25p^2=16p | | v+18=11 |

Equations solver categories